Sporadic Progressive Symmetric Erythrokeratoderma: Classical Presentation of a rare Condition - Kompal Agarwal; Sudha Agrawal; Anju Pradhan (Nepal Journal of Dermatology, Venereology & Leprology)
Progressive symmetrical erythrokeratodermia (PSEK) is a rare autosomal dominant genodermatosis presenting in infancy or early childhood. An 11-year-old male presented with a history of pruritic, erythematous, scaly, hyperkeratotic plaques first noted at 5 years of age, with no history of similar lesions in the family. Cutaneous examination revealed multiple, irregularly shaped, erythematous plaques with fine, shiny white, adherent scaling distributed symmetrically over the face, trunk, inguinal area, bilateral axillae and extensor surfaces of limbs. Palmoplantar keratoderma was present with thickened, yellowish discolored nails. No systemic abnormality was found. The histopathological findings were consistent with PSEK. The case is being reported to increase the awareness about this rare disease.